Thursday

April 17, 2014

April 17, 2014

Posted by **mike** on Saturday, September 15, 2012 at 10:16pm.

- college algebra -
**Steve**, Saturday, September 15, 2012 at 10:37pmjust plug in the values:

f(x) = 4x+3

f(x+h) = 4(x+h)+3

f(x+h)-f(x) = (4x+4h+3) - (4x+3) = 4h

(f(x+h) - f(x))/h = 4h/h = 4

- algebra 2 -
**Nicole**, Monday, April 15, 2013 at 1:16am4x-1 / 2x^2+3

**Related Questions**

Algebra - I am really having problems with monomials: Please help! Simplify: 4x^...

Math - Not sure how far to take this problem down. The directions say to ...

Algebra 2 - (4x^4-4x^2-x-3)divided by(2x^2-3) quotient an remainder?

algebra - 4x^3-5x^2-10x-3 divided by 4x+3

Algebra 2 - (4x^3-4x^2-x-3)divided by(2x^2-3)

Pre-algebra - I have some practice problems, and I need to have them worked out...

Pre-algebra - I have some practice problems, and I need to have them worked out...

college algebra - -4x^2y(-4x^3y^5)

math - Multiplying and Dividing Rational Expressions: 2) x^2-8x+7/x^2+6x-7 = (x-...

math - Multiplying and Dividing Rational Expressions: 2) x^2-8x+7/x^2+6x-7 = (x-...